Penyuluhan Kewirausahaan dalam Meningkatkan Motivasi dan Kesiapan Berwirausaha di Era Digital - Arya Darmawan; Zulkarnaini; Meita Pragiwani; Sri Handoko Sakti; Irfan Arif Husen; Farmansyah Maliki (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2026)
This Community Service Program aimed to enhance students’ understanding of entrepreneurship and increase their motivation to pursue entrepreneurial activities as an alternative career path. The program was conducted on April 16, 2026, at SMA Negeri 36 Jakarta by lecturers from STIE Indonesia Jakarta. The methods employed included lectures, case study presentations, interactive discussions, and question-and-answer sessions. The materials covered fundamental entrepreneurship concepts, business opportunities, entrepreneurial characteristics, and real-life cases of successful and unsuccessful businesses. The results indicated that the program effectively improved students’ understanding of entrepreneurship and increased their interest in developing business ideas. Students actively participated in discussions and demonstrated greater awareness of entrepreneurship as a means of achieving economic independence and creating employment opportunities. Evaluation results also showed an increase in students’ motivation to learn more about entrepreneurship and explore their creative potential. The program concludes that entrepreneurship education can play an important role in fostering entrepreneurial mindsets among young people and preparing them to face future economic challenges.